Atuação de enfermeiros, enfermeiras e agentes comunitários de saúde na década de 80: a experiência de Braga, RS - Barros, Camilla Silva de (2022)
The study is part of a larger research, THE CONSTRUCTION OF THE SUS IN MUNICIPALITIES IN THE INTERIOR OF RS: INVENTORY OF EXPERIENCES IN HEALTH PROMOTION AND PRIMARY CARE, registered in the UFSM Projects Portal under number 055865. It is an effort of three institutions: UFSM, Unijuí and UFRGS. This report highlights the performance of male and female nurses in the community health project in Braga and the training and performance of Community Health Agents. The general objective was to know aspects of the performance of nurses, nurses and Community Agents in the experience of Community Health in Braga, RS, between the years 1983 and 1988. The specific objectives were: to identify aspects of the training of nurses who worked in the project of Community Health in Braga between 1983 and 1988, to describe the performance of nurses in management and care within the scope of the Community Health Project in Braga between 1983 and 1988 and to understand the context of the work of Community Health Agents in Health that participated in the Braga Community Health project between 1983 and 1988. It is a qualitative research, based on a case study and fourth generation evaluation. Open interviews, focus groups and document analysis were carried out. The study of the research material resulted in two categories: training and performance of nurses and training and performance of Community Health Agents (ACS). During their training, the nurses participated in the student movement and made connections with community health projects. FIDENE - Foundation for Integration, Development and Education of the Northwest of the State of RS, current sponsor of Unijuí (Regional University of the Northwest of RS) played an important role in making this experience viable: it created a less traditional course and articulated human and financial resources. The importance of the experience of Murialdo and the cooperative Unochapecó for the training of nurses is highlighted. In the experience on the agenda, they participated in the design of the project, worked with communities and in hospital care, in addition to carrying out training for Community Health Agents (ACS). The agents had an important bond with their communities, by whom they were elected. They were volunteers and performed procedures (bandages, injections) and worked with teas, ointments and procedures that constituted the scope of the training process. They were responsible for the connection between the community, the service at the posts and the hospital. The support for the ACS stands out in the work of the nurses. The inventory of training and practices, at this moment, still has gaps in knowledge, but the research contributes to the history of nursing practices and the participation of nurses in the experiences that preceded the SUS in the region and is a contribution to contemporary proposals for insertion of nurses with so-called advanced practices. Regarding the ACS, the institutionalization of the Family Health Program (PSF) and later the ESF (Family Health Strategy) did not have the capacity to dialogue with what the territory had accumulated, disregarded the experience and silenced its protagonists.